Nanotechnology and biomimetics with 2-D protein crystals. - Sleyter, U.B.
The application potential of crystalline bacterial cell surface layers (S-layers) as nature-tailored supramolecular structures is described. The fabrication of supramolecular devices requires molecules that are capable of interlocking in a well-defined manner. Thus, molecular self-assembly systems that exploit the molecular-scale manufacturing precision of biological systems are prime candidates for supramolecular engineering. Although self-assembly of molecules is an ubiquitous strategy of morphogenesis in nature, researchers in the area of molecular nanotechnology and biomimetics are only beginning to exploit its potential for the functionalization of surfaces and interfaces as well as for the production of biomimetic membranes and encapsulation systems. This article presents an overview of a new approach in nanostructure technology and biomimetics based on crystalline bacterial cell surface layers.
Keywords: S-layers.; Biological systems; Crystalline bacterial cell surface layers; Interfaces; Molecular self-assembly.; Molecular-scale manufacturing precision; Morphogenesis; Nanostructure technology; Supramolecular devices fabrication; Supramolecular engineering; Surfaces functionalization